Pottery : 20 mindful makes to reconnect head, heart & hands - Davidson, Lucy (Graphic designer) (Conscious crafts., 2021)
Learn how to create simple, modern makes -- all without the need for a wheel or kiln. Featuring basic techniques and simple clay recipes, Lucy Davidson provides ideas for making and decorating 20 playful pottery pieces with clear step-by-step instructions and life-affirming mindful quotes, accompanied by clean photography and contemporary illustrations. From plant hanger pots to tealight holders, festive decorations to serving dishes -- there's plenty to enhance your home and your wellbeing.